Improving children's critical thinking skills in elementary school through the development of problem based learning and HOTS models - Radiansyah, Radiansyah; Sari, Raihanah; Jannah, Fathul; Prihandoko, Yogi; Rahmaniah, Nahdia Fitri (Trigin Institute, 2023)
The purpose of this research is to find learning model steps that are able to develop critical thinking skills, as well as to analyze students' learning outcomes. The combination of Problem Based Learning (PBL) and Higher Order Thinking Skills (HOTS) model steps is a learning strategy that is expected to be implemented effectively. The method used in this research is Research and Development. The research stages can be broken down as follows: (1) the preparation stage, (2) the Problem Based Learning and HOTS Model Development stage, (3) the model effectiveness analysis stage. The results of the research on the development of the Problem Based Learning and HOTS Model obtained an increase in students' critical thinking skills of 42.50, and learning outcomes with an average score of 86.14. Students' critical thinking gain of 0.75 is included in the high category. The conclusion from the research results is that the Problem Based Learning and HOTS models are effectively implemented in learning at SDN Kertak Hanyar, in other words can improve critical thinking skills, and student learning outcomes. As a follow-up to the results of this study, a wider dissemination of the steps of the Problem Based Learning and HOTS model will be carried out to teachers at Banjar Regency elementary schools